2005
DOI: 10.1093/aob/mcj027
|View full text |Cite
|
Sign up to set email alerts
|

Floral Nectar Production and Nectary Anatomy and Ultrastructure of Echinacea purpurea (Asteraceae)

Abstract: The abundance of mitochondria suggests an eccrine mechanism of secretion, although dictyosomal vesicles may contribute to a granulocrine process. Phloem sap evidently is the main contributor of nectar carbohydrates. From the sieve elements and companion cells, an apoplastic route via intercellular spaces and cell walls, leading to the pores of modified stomata, is available. A symplastic pathway, via plasmodesmata connecting sieve elements to companion, parenchyma and epidermal cells, is also feasible. Uncolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 54 publications
(85 reference statements)
11
63
0
2
Order By: Relevance
“…They contain an epidermis in addition to a nectar and a subnectary parenchyma (Stpiczy nska et al, 2005;Wist and Davis, 2006;Kaczorowski et al, 2008;Wenzler et al, 2008;Fig. 2A).…”
Section: Two Types Of Nectary Structures Harbor Unique Secretion Systemsmentioning
confidence: 99%
“…They contain an epidermis in addition to a nectar and a subnectary parenchyma (Stpiczy nska et al, 2005;Wist and Davis, 2006;Kaczorowski et al, 2008;Wenzler et al, 2008;Fig. 2A).…”
Section: Two Types Of Nectary Structures Harbor Unique Secretion Systemsmentioning
confidence: 99%
“…Reclamation of nectar components in Fritillary is facilitated by the presence of micro-channels or pores in the cuticle that covers the secretory epidermis, as in Echinacea purpurea L. (Moench) (Wist and Davis 2006), P. chlorantha (Stpiczyńska 2003a) and C. pepo (Nepi et al 2001). Also, in F. meleagris, the efficiency of nectar resorption is improved by the wall ingrowths present in the cells of the nectariferous epidermis and parenchyma, and these were still present at the final stages of anthesis, when nectar resorption occurs.…”
Section: Nectar Secretion and Resorptionmentioning
confidence: 99%
“…Several authors have addressed floret phenological studies (Neff & Simpson 1990;Cerana 2004;Hong et al 2008;Huang et al 2012) or capitulum phenological studies (Brouillet & Simon 1979;Corral et al 2004;Bull-Hereñu & Arroyo 2009), but few researchers have addressed them together (Wild et al 2003;Wist & Davis 2006) as in the present study. The anthesis period is defined as the length of time in which individual florets remain open with fresh-looking perianth, pistil and stamens exposed (Primack 1985;Ashman & Schoen 1995).…”
Section: Discussionmentioning
confidence: 96%
“…Several authors (Vogel 1998;Wist & Davis 2006;Bernardello 2007;Wist & Davis 2008) have reported nectar production for the Asteraceae. These authors describe secretions coming from the nectary disk present at the base of the style; no report exist to date of nectar secretion coming from other parts of the floret in the Asteraceae.…”
Section: Discussionmentioning
confidence: 99%